Candidate drugs against SARS-CoV-2 and COVID-19 - McKee, Dwight L.; Sternberg, Ariane; Stange, Ulrike; Laufer, Stefan; Naujokat, Cord (Pharmacological research, 2020)
Outbreak and pandemic of coronavirus SARS-CoV-2 in 2019/2020 will challenge global health for the future. Because a vaccine against the virus will not be available in the near future, we herein try to offer a pharmacological strategy to combat the virus. There exists a number of candidate drugs that may inhibit infection with and replication of SARS-CoV-2. Such drugs comprise inhibitors of TMPRSS2 serine protease and inhibitors of angiotensin-converting enzyme 2 (ACE2). Blockade of ACE2, the host cell receptor for the S protein of SARS-CoV-2 and inhibition of TMPRSS2, which is required for S protein priming may prevent cell entry of SARS-CoV-2. Further, chloroquine and hydroxychloroquine, and off-label antiviral drugs, such as the nucleotide analogue remdesivir, HIV protease inhibitors lopinavir and ritonavir, broad-spectrum antiviral drugs arbidol and favipiravir as well as antiviral phytochemicals available to date may limit spread of SARS-CoV-2 and morbidity and mortality of COVID-19 pandemic.